DE LA INVESTIGACIÓN A LA DIDÁCTICA: HERRAMIENTAS PARA DETECTAR Y MEJORAR PAUTAS DE TRADUCCIÓN. - Martín De León, Celia (Hermeneus, 2016)
Translator training has traditionally focused on the translation product, particularly on the detection and correction of errors. Translation processes have also been the focus of research since the 1980s, and the research tools developed and applied in this field can be used in the classroom to help students detect and improve their translation patterns. This work studies the didactic application of a key logger (Translog) and a screen recorder (FlashBack Express). The study is exploratory and was conducted with a third-year student of a Translation and Interpreting. She translated two short stories using Translog or FlashBack Express to collect the translation process data, and answered three questionnaires. The main results indicate that Translog is very useful to help one to become aware of self-patterns and strategies of translation. Furthermore, FlashBack Express can be a useful complement to Translog because it records Internet searches.